Development Studies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Centre for Development Research (ZEF) in Bonn, Germany is offering an international doctoral programme for young scientists engaged in political and social science, economics, agriculture, geography, ecology and management of natural resources....